Analysis of micro coil geometric features for mems-based fluxgate magnetometer - Sulaiman, Nadzril (2017)
This research presents a multi variant structure of fluxgate magnetometer. The core of fluxgate magnetometer is made of soft iron material. It also consists of sensing and driving coils made of copper having conductivity of 5.8*10^7[S/m]. Magnetic flux density of fluxgate sensors is simulated by considering different core structures that include E-shaped core (adjacent coils), square shaped core, rectangular shaped core, E-shaped core (centre tapped coil) and triangular shaped core. These designs consist of primary and secondary coils, which are used as driving coil and sensing coil respectively. In addition, these different types of cores have been analysed by varying the successive coil turns through which magnetic flux flow is measured. All these structures are designed and simulated by using a FEM (Finite Element Method) tool known as COMSOL multiphysics. Furthermore, results of all assumed structures are compared to finalize the better design among all the chosen structures. Consequently, triangular shaped structures result in a good sensitivity range of ±0.02mT regardless of its size. The fluxgate magnetometer is suitable for various applications including power transformer and inverter for interior magnetic core fault detection and high sensitivity.